The saturation degree of fatty acids and their derived acylcarnitines determines the direct effect of metabolically active thyroid hormones on insulin sensitivity in skeletal muscle cells. Issue 2 (11th September 2018) - Giacco, Antonia; Delli Paoli, Giuseppe; Senese, Rosalba; Cioffi, Federica; Silvestri, Elena; Moreno, Maria; Ruoppolo, Margherita; Caterino, Marianna; Costanzo, Michele; Lombardi, Assunta; Goglia, Fernando; Lanni, Antonia; et al.
ABSTRACT: Using differentiated rat L6 cells, we studied the direct effect of 3, 5, 3′‐triiodo‐l ‐thyronine (T3) and 3, 5‐diiodo‐l ‐thyronine (T2) on the response to insulin in presence of fatty acids with a varying degree of saturation. We found that T3 and T2 both invert the response to insulin by modulating Akt Ser473 phosphorylation in the presence of palmitate and oleate. Both hormones prevented palmitate‐induced insulin resistance, whereas increased insulin sensitivity in the presence of oleate was reduced, with normalization to (or, in the case of T3, even below) control levels. Both hormones effectively reduced intracellular acylcarnitine concentrations. Interestingly, insulin sensitization was lowered by incubation of the myotubes with relevant concentrations of palmitoylcarnitines (C16) and increased by oleylcarnitines and linoleylcarnitines (C18:1 and C18:2, respectively). The efficiency of mitochondrial respiration decreased in the order palmitate‐oleate‐linoleate; in the presence of palmitate, only T3 increased ATP synthesis‐independent cellular respiration and mitochondrial respiratory complex activities. Both hormones modulated gene expression and enzyme activities related to insulin sensitivity, glucose metabolism, and lipid handling. Although T2 and T3 differentially regulated the expression of relevant genes involved in glucose metabolism, they equally stimulated related metabolic activities. T2 and T3 differentially modulated mitochondrial fatty acid uptake and oxidation in the presence of each fatty acid. The results show that T2 and T3 both invert the fatty acid‐induced response to insulin but through different mechanisms, and that the outcome depends on the degree of saturation of the fatty acids and their derived acylcarnitines.—Giacco, A., delli Paoli, G., Senese, R., Cioffi, F., Silvestri, E., Moreno, M., Ruoppolo, M., Caterino, M., Costanzo, M., Lombardi, A., Goglia, F., Lanni, A., deLange, P. The saturation degree of fatty acids and their derived acylcarnitines determines the direct effect of metabolically active thyroid hormones on insulin sensitivity in skeletal muscle cells. FASEB J. 33, 1811–1823 (2019). www.fasebj.org